Can native vegetation recover after slash pine cultivation in the Brazilian Savanna? - Real de Abreu, Rodolfo Cesar; de Assis, Geissianny Bessao [UNESP]; Frison, Sergianne [UNESP]; Aguirre, Andrea; Durigan, Giselda [UNESP] (Elsevier B.V., 2011)
There is a widespread view that forest plantations with exotic species are green deserts, unable to sustain biodiversity. Few studies have demonstrated, however, that planted stands of exotic trees have a greater negative effect on the plant diversity of savanna vegetation. We compared the native woody flora under four stands of slash pine of about 45 years old with four stands where the previously existing native Cerrado vegetation was preserved and protected from disturbances for the same period, has changed into dense vegetation - the "cerradao", at Assis municipality, São Paulo State, Brazil. Aiming at understanding the potential ecological filters driving these communities, we assessed air and soil humidity, light availability and classified the native species on the basis of shade tolerance, dispersal syndrome and biomes in which they occur (Atlantic Forest or Cerrado). We recorded an average of 70 (+/- 13) species under pine stands and 54 (+/- 16) species in cerradao. of the total of 136 species recorded, 78 occurred in both habitats, eight were exclusive to the "cerradao" (shade tolerant and also occurring in forest ecosystems) and 18 were recorded only under pine stands (82% heliophytic, exclusive to the Cerrado biome). Among the functional attributes and abiotic variables analyzed, only light availability explained the floristic differences found. Since richness was higher under pine, we refuted the hypothesis that exotic species constrain the establishment of the native species richness in the understory. on the other hand, the dark environment under the closed-canopy of the "cerradao" acts as a filter inhibiting the establishment of typical Cerrado species. Since pine stands, if managed in long cycle, maintain a reasonable pool of Cerrado endemic species in the understory pine plantations may be a good starting point for savanna restoration. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Forest plantations; Exotic species; Savanna; Pinus elliottii Engelm.; Intermediate disturbance hypothesis